2019
DOI: 10.3389/fonc.2019.01164
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-Based Machine Learning Technology Enables Better Differentiation Between Glioblastoma and Anaplastic Oligodendroglioma

Abstract: Purpose: The aim of this study was to test whether radiomics-based machine learning can enable the better differentiation between glioblastoma (GBM) and anaplastic oligodendroglioma (AO).Methods: This retrospective study involved 126 patients histologically diagnosed as GBM (n = 76) or AO (n = 50) in our institution from January 2015 to December 2018. A total number of 40 three-dimensional texture features were extracted from contrast-enhanced T1-weighted images using LIFEx package. Six diagnostic models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…During the process of radiomics model building, we investigated different techniques, including supervised machine learning and LASSO regression analysis, to explore characteristics and identify the optimal features for model construction. LASSO turned out to several advantages as it reduces redundancy, dependency, and dimensionality of the features and thus enhances model accuracy 19 . In addition, LASSO enables the generation of interpretable models using variable selection and regularization as well as integration of selected features into a radiomics signature 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of radiomics model building, we investigated different techniques, including supervised machine learning and LASSO regression analysis, to explore characteristics and identify the optimal features for model construction. LASSO turned out to several advantages as it reduces redundancy, dependency, and dimensionality of the features and thus enhances model accuracy 19 . In addition, LASSO enables the generation of interpretable models using variable selection and regularization as well as integration of selected features into a radiomics signature 19 .…”
Section: Discussionmentioning
confidence: 99%
“…LASSO turned out to several advantages as it reduces redundancy, dependency, and dimensionality of the features and thus enhances model accuracy 19 . In addition, LASSO enables the generation of interpretable models using variable selection and regularization as well as integration of selected features into a radiomics signature 19 . As for classification algorithms, we used both binary and multinomial classification.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to finding the best diagnostic model, we also found that some of the models performed poorly. A previous study used LDA and SVM classifier machine learning methods to identify glioblastoma (GBM) and anaplastic oligodendrocytoma (AO), and found that the AUC of testing set was all above 0.90 ( 47 ). However, in our study, these two classification algorithms do not show good diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…In neuroradiology, machine learning models have started to be used in grading glial tumors. Especially in the preoperative period, to predict molecular subtype and survival [15][16][17][18] . Our study developed a machine learning model for predicting survival based on texture analysis data obtained from contrasted T1-weighted images obtained in the preoperative period.…”
Section: Discussionmentioning
confidence: 99%